If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1(4y + 3) + -1(-3y + -6) = 2 Reorder the terms: -1(3 + 4y) + -1(-3y + -6) = 2 (3 * -1 + 4y * -1) + -1(-3y + -6) = 2 (-3 + -4y) + -1(-3y + -6) = 2 Reorder the terms: -3 + -4y + -1(-6 + -3y) = 2 -3 + -4y + (-6 * -1 + -3y * -1) = 2 -3 + -4y + (6 + 3y) = 2 Reorder the terms: -3 + 6 + -4y + 3y = 2 Combine like terms: -3 + 6 = 3 3 + -4y + 3y = 2 Combine like terms: -4y + 3y = -1y 3 + -1y = 2 Solving 3 + -1y = 2 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + -1y = 2 + -3 Combine like terms: 3 + -3 = 0 0 + -1y = 2 + -3 -1y = 2 + -3 Combine like terms: 2 + -3 = -1 -1y = -1 Divide each side by '-1'. y = 1 Simplifying y = 1
| 7(3c-5)= | | 5x+4=-(x-22) | | 3x+5+2x=45 | | 20x-y=2 | | 13x+2y=-55 | | 2x^2-4=204 | | 5n+7=17 | | 2[-2(x-4)+5(x-2)]= | | -8t=27+t | | -t=27+t | | 2[x-(2x+4)+3]=2(x+1) | | 5(3x-4)-3=6x+7 | | 6(4x-y)-2(5x+2y)= | | x(x-3)(x+4)=0 | | 3(-4x+8)=-x | | 61-2x=16x+17 | | 61-2x=16x+18 | | 2s-8= | | 12-8x=72-43x | | 5(8x-2y)-5(2x+3y)= | | 3x-5y+8x+y= | | -2x-6=15-3x | | 5x+10=-107-8x | | 7y-7=5y+13 | | 8y+4(6+y)=3(y-2)+10y | | 3t-6=6t+30 | | 149-3x=6x+14 | | 2(x+4)+3=2x+6 | | -50-4x=118+2x | | 2xyz=18 | | 23b+9=4b+66 | | 150-4x=118+2x |